Short-term results of Weils osteotomy in patients with propulsive metatarsalgia - Hernández-Martínez, J C; Vázquez-Escamilla, J; Coronado-Puente, M (Acta ortopédica mexicana, 2017)
Metatarsalgia is the most common reason for consultation in orthopedic pathology of the foot. The key to its treatment lies in the correct determination of the symptoms, which are biological, morphological and mechanical alterations responsible for pain. Weil´s osteotomy is commonly used for multiple forefoot pathologies, including metatarsalgias. We included patients with first-line failure syndrome and associated mechanical metatarsalgia-producing deformities. The minimum follow-up was six months. All individuals were interviewed with a standardized questionnaire based on the AOFAS, a survey to know their degree of satisfaction about the surgery. Twelve female subjects with a mean age of 51 years were recruited between March and September of 2013. Seven right feet, five left. The AOFAS values improved only in six, in which an excellent result was obtained; five rated them as good and six as unsatisfactory. In a very small series, postoperative complications were observed when the shortening of the metatarsal was greater than four millimeters, with the appearance of stiffness (floating finger).